2000
DOI: 10.1159/000031176
|View full text |Cite
|
Sign up to set email alerts
|

Are All Leucodepleted Platelet Concentrates Equivalent?

Abstract: Background and Objectives: A number of technologies are available for the production of leucocyte–depleted platelet concentrates (PCs). This study compared the characteristics of PCs prepared by three commonly used techniques. Materials and Methods: In total, fifteen units of leucoyte–depleted PCs prepared by the Cobe LRS Turbo apheresis system, Haemonetics MCS+ with in–line filter and filtration of PCs derived from pooled buffy coats (BCs) were transferred into the same standard container. Markers to assess s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…Our observation is in contrast to two former MP studies in PC prepared from whole blood [23], but also in apheresis concentrates [24], where increasing PMP levels were observed during storage time. However, these two studies identified MP only by their dimension using beads, which attributed to their much higher light scattering properties compared to MP of similar diameter will lead to inappropriate setting of flow cytometry thresholds and therefore may produce incorrect results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our observation is in contrast to two former MP studies in PC prepared from whole blood [23], but also in apheresis concentrates [24], where increasing PMP levels were observed during storage time. However, these two studies identified MP only by their dimension using beads, which attributed to their much higher light scattering properties compared to MP of similar diameter will lead to inappropriate setting of flow cytometry thresholds and therefore may produce incorrect results.…”
Section: Discussioncontrasting
confidence: 99%
“…It is well known that platelet concentrates (PC) contain MP, which may be related to the increased incidence of venous thrombosis and embolism following platelet transfusion [21,22]. MP have been detected in PC prepared from whole blood [23] and in apheresis concentrates [24] and have been related to harvest conditions and storage stress. However, the cellular origin or activation status of MP was not investigated in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Development in medical sciences, including transplantation programs, has significantly increased the demand for platelets (PLT) 1,2 . The last two decades have observed an inclination toward the use of apheretic PLT rather than random donor PLT 3 .…”
Section: Introductionmentioning
confidence: 99%
“…While the demand for apheresis platelets (PLTs) has been steadily increasing, 1‐3 the recruitment and retention of voluntary and eligible blood donors becomes more and more difficult 4 . High‐dose plateletpheresis enables the collection of multiple units from the same donor in a single donation and may have the potential to counteract this problem and to reduce both costs and risks inherent with allogenic transfusion 5‐8 .…”
mentioning
confidence: 99%